Junie B. Jones and the stupid smelly bus - Park, Barbara; Brunkus, Denise (New York : Random House, 1992)
In her own words, a young girl describes her feelings about starting kindergarten and what she does when she decides not to ride the bus home.
Series numbering started in volume five.
"A First stepping stone book."
Keywords: Kindergarten -- Fiction; School buses -- Fiction; Schools -- Fiction